Maternal Displacements during Pregnancy and the Health of Newborns - Stefano Cellini; Livia Menezes; Martin Foureaux Koppensteiner (Institute of Labor Economics (IZA), 2022)
In this paper, we estimate the effect of maternal displacements during pregnancy on birth outcomes by leveraging population-level administrative data from Brazil on formal employment linked to birth records. We find that involuntary job separation of pregnant single mothers leads to a decrease in birth weight (BW) by around 28 grams (-1% ca.) and an increase in the incidence of low BW by 10.5%. In contrast, we find a significant positive effect on the mean BW and a decrease in the incidence of low BW for mothers in a marriage or stable union. We document more pronounced negative effects for single mothers with lower earnings and no effect for mothers in the highest income quartile, suggesting a mitigating role of self-insurance from savings. Exploiting variation from unemployment benefits eligibility, we also provide evidence on the mitigating role of formal unemployment insurance using a Regression Discontinuity design exploiting the cutoff from the unemployment insurance eligibility rule.
Keywords: D14; I10; J65; 330; dismissals; birth outcomes; informal insurance; unemployment insurance